1992
DOI: 10.1007/bf02536117
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid and mineralocorticoid hormones depress liver Δ5 desaturase activity through different mechanisms

Abstract: The effects of 11-deoxycorticosterone and aldosterone on liver delta 5 desaturase activity were examined. Both steroid hormones significantly depressed the conversion of [1-14C] eicosatrienoic acid to arachidonic acid. However, the mechanism of action of each of these hormones was different. The effect of 11-deoxycorticosterone was mediated by a soluble protein present in the liver cytosolic fraction. The biological activity of this protein, having a molecular weight lower than 25 kDa, was impaired by trypsin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Previous experiments from our laboratory demonstrated that glucocorticoids can induce a soluble second messenger recovered as a low molecular weight peptide in the 110,000 × g supernatant fraction from liver cell homogenates. The addition of this factor modulates desaturase activities in in vitro enzyme assays (39,54,55). It was our aim to investigate if calcium deprivation could modify desaturase activity through a similar mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments from our laboratory demonstrated that glucocorticoids can induce a soluble second messenger recovered as a low molecular weight peptide in the 110,000 × g supernatant fraction from liver cell homogenates. The addition of this factor modulates desaturase activities in in vitro enzyme assays (39,54,55). It was our aim to investigate if calcium deprivation could modify desaturase activity through a similar mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Production of AA from LA involves three key enzymatic steps: Δ-6-desaturation to form 18:3n6 (GLA), followed by elongation to 20:3n6 (dihomo-GLA (DGLA)) and a Δ-5-desaturation step to produce 20:4n6. Thus, LA-enriched formulas cannot worsen inflammation simply because the activity of the enzymes Δ-5-desaturase and Δ-6-desaturase are severely compromised during critical illness by the release of stress and catabolic hormones (for example, glucocorticoids and catecholamines) [33,34] limiting the ability to form AA despite the provision of LA [35]. GLA is a metabolite of LA that can bypass the decreased expression of Δ-6-desaturase.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, these outcomes may be attributable to several compounding factors. While ∆6 desaturation of both LNA to stearidonic acid (18:4n-3) and LA to GLA is a rate-limiting step under normal conditions, evidence exists to suggest that ∆6-desaturase activity is further reduced under conditions that foster release of epinephrine and other stress-associated hormones (29)(30)(31). This hormonal milieu can be found in traumatized or acutely septic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, formation of EPA from LNA is subject to the activity of ∆6 desaturase, a rate-limiting enzyme that catalyzes the initial desaturation of LNA to stearidonic acid (18:4n-3) (27,28). Compounding this quandary are reports that the stress hormones, i.e., epinephrine (29,30), ACTH (30) or glucocorticoids (31), have an inhibitory effect on both the ∆6 and ∆5 desaturases involved in LNA desaturation to EPA. Reduced activity of ∆6 desaturase may also limit GLA formation from dietary LA, potentially retarding formation of DHGLA and its metabolite, PGE 1 .…”
mentioning
confidence: 99%